2003
DOI: 10.1038/sj.bjc.6601330
|View full text |Cite
|
Sign up to set email alerts
|

Multiple and synergistic deregulations of apoptosis-controlling genes in pancreatic carcinoma cells

Abstract: Inability to die by apoptosis is one of the reasons for the deregulated growth of tumour cells and the frequently observed failure of chemotherapy. In this study we thought to identify the common and functionally important characteristics responsible for the apoptosis resistance of pancreatic tumour cells. We analysed cell surface expression level of death receptors CD95 and TRAIL-R1-4 as well as the expression profile of sixteen apoptosis-relevant proteins in five pancreatic carcinoma cell lines Capan1, Colo3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 37 publications
7
48
0
Order By: Relevance
“…We show here that XIAP is overexpressed in the majority of human pancreatic cancers, as assessed by immunohistochemistry, confirming for the first time data that have been reported previously only in cell line models (13,14). Although the numbers of cases analyzed are relatively small, the trend clearly underscores that XIAP up-regulation is a common phenomenon in pancreatic cancer.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We show here that XIAP is overexpressed in the majority of human pancreatic cancers, as assessed by immunohistochemistry, confirming for the first time data that have been reported previously only in cell line models (13,14). Although the numbers of cases analyzed are relatively small, the trend clearly underscores that XIAP up-regulation is a common phenomenon in pancreatic cancer.…”
Section: Discussionsupporting
confidence: 74%
“…Because many therapeutic modalities principally act by promoting apoptosis, alterations in this intracellular cascade can render neoplastic cancer cells resistant to therapy (6). A family of endogenous antiapoptotic proteins known as inhibitors of apoptosis proteins (IAP), which bind and repress proapoptotic caspases in their quiescent 'zymogen' state, is frequently overexpressed in both solid and hematologic malignancies (7 -12), including pancreatic cancer (13,14). It is postulated that IAPs may be a major cause of the resistance to chemoradiation therapy -induced apoptosis observed in neoplastic cells; therefore, blockade of IAP function while simultaneously initiating cellular apoptosis would have the effect of overcoming this resistance state (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…In some pancreatic carcinoma cell lines, we observed a slight increase in cell viability upon treatment with low concentrations of TRAIL (Figure 1b) in line with our previous findings that TRAIL may trigger proliferation under certain circumstances (Ehrhardt et al, 2003). Based on these studies, we selected PaTuII, PancTu1, ASPC1 and DanG pancreatic carcinoma cells, which were relatively resistant towards TRAIL, and Colo357 as a prototype TRAIL-sensitive cell line to identify molecular (Hinz et al, 2000;Trauzold et al, 2003). This indicates that resistance to TRAIL is presumably caused by mechanisms acting further downstream in the TRAIL signaling pathway.…”
Section: Trail-induced Cell Death In Pancreatic Carcinoma Cellssupporting
confidence: 53%
“…The reason for this spectrum of response to TRAIL-R activation is due to the complex downstream regulation of the cell death pathway. Intracellular levels of pro-and antiapoptotic factors such as cFLIP (Kim et al, 2000;Sayers et al, 2003), XIAP Chawla-Sarkar et al, 2002), BCL-2 family members (Burns and El-Deiry, 2001;LeBlanc et al, 2002), and DISC formation and caspase 8 activity (Trauzold et al, 2003) have been reported to regulate cell sensitivity to TRAIL-induced programmed cell death in both tumour and normal cells. Although TRAIL decoy receptors have been implicated in the regulation of TRAIL signalling, the presence of decoy receptors (DcR1, DcR2) are not a factor in resistance to HGS-ETR1 activity, as HGS-ETR1 does not bind to either of these receptors (Figure 1).…”
Section: Discussionmentioning
confidence: 99%